Hydrogen cyanamide improves endodormancy release and blooming associated with endogenous hormones in 'Summit' sweet cherry trees. Issue 1 (2nd January 2017) - Wang, Lei; Zhang, Caixi; Huang, Jiancheng; Zhu, Lina; Yu, Xiuming; Li, Jiefa; Lou, Yusui; Xu, Wenping; Wang, Shiping; Ma, Chao
ABSTRACT: A trial was conducted to verify the effect of hydrogen cyanamide (HC) application on endodormancy release and blooming of 'Summit' sweet cherry trees, as well as on endogenous gibberellic acids (GAs) and abscisic acid (ABA) levels which were identified and quantified by gas chromatography/mass spectrometry in branches with spurs. Results showed that HC efficiently hastened endodormancy release and budbreak, shortened blooming duration and improved fruit set. Furthermore, bioactive GAs play different roles in the process of endodormancy release and blooming. GA3 was recognised as the highest isomer of bioactive GA and was closely related with endodormancy release improved by HC treatment as well as GA4 . GA7 displayed a rapid increase when buds went into the burst stage and associated with promoted budburst and blooming by HC treatment. GA1 showed irregular changes during this process. A higher GAs:ABA ratio was observed in HC-treated 'Summit' branches from endodormancy release until full bloom. However, a reciprocal pattern occurred thereafter due to senescence of the flowers.